Analysis of Faith, Islam, and Ihsan Material in Learning Aqidah Morals at Junior High School - Adona, Putri; Yahya, Muhamad; Sospita, Devi (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2024)
The integration of Iman, Islam, and Ihsan in learning materials is very important as a source of understanding for students regarding the formation of aqidah amidst the rising issues of globalization and moral decadence. Based on this, in this research, the author wants to analyze the material on Faith, Islam, and Ihsan in the teaching of Aqidah Akhlak at Madrasah Tsanawiyah. The research method used is a qualitative method with a content analysis approach, the main source is the Aqidah Akhlak textbook published by the Ministry of Religion of the Republic of Indonesia. After carrying out an in-depth analysis, the author found that the structure of the Aqidah Akhlak material at Madrasah Tsanawiyah related to Faith, Islam and Ihsan consists of three sub-themes. The three sub-themes are i) Basic Concepts of Islamic Creed, ii) Basic Concepts of Faith, Islam, and Ihsan, iii) the Relationship between Faith, Islam, and Ihsan. In the future, the author hopes that this research will have a positive impact, especially in madrasas as formal educational institutions with the characteristic of instilling Islamic values in their students.